Effectiveness and Challenges: The Current Situation of Electronic Health Records (EHRs) to Improve Health Care Outcomes - Myra Cusi Britiller; Aimee M. Amponin; Cecilia C. Pring (University of Muhammadiyah Semarang, 2023)
Background. In the Philippines, although software for Electronic Health Records (EHRs) is still new, knowledge about EHRs benefits is increasing.Objective: This study investigated the effectiveness of electronic health records to health care outcomes at selected health facilities in the National Capital Region (NCR) and CALABARZON regions of the Philippines. The effectiveness of the current EHRs in government and private health facilities were determined in terms of quality patient care, patient engagement, support team-based care, workload, and data liquidity; and the challenges facing health providers in the implementation of electronic health records were identified.Methods. The research utilized the descriptive, cross-sectional design. Three hundred seven (N=307) health providers from the medical, nursing, and paramedical departments were the study participants. A three-part adapted questionnaire was the main tool used for data collection. Mean, standard deviation, and Mann-Whitney & Kruskal-Wallis’s tests were utilized for data analysis.Results. The results revealed that in the Philippines, EHRs are moderately effective in improving health care outcomes. EHRs effectiveness is primarily achieved through better access and retrieval of health information. EHRs implementation poses major challenges in the Philippines’ health facilities which are central to socio-economic and organizational factors.Conclusions. The more effective the use of EHR systems, the greater the challenges experienced by care providers and health facilities.